Culturally Responsive Teaching for Deep Learning: Exploring Pre-Service Teachers’ Pedagogical Competence Across the Instructional Cycle - Wulandari, I Gusti Ayu Putu Arya; Kadek Rahayu Puspa Dewi; Gusti Ayu Made Arna Putri; Koming Ari Denawati; Handriyani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine pre-service teachers’ pedagogical competence in implementing Culturally Responsive Teaching (CRT) to support deep learning pedagogy during mathematics lessons observed in their teaching practicum and to identify points at which implementation weakened across the instructional cycle. A qualitative descriptive design was employed, with structured 1–4 observation ratings used solely as descriptive supporting evidence rather than as a separate quantitative strand. Observations and document analysis involved 30 pre-service teachers, while interviews were conducted with 10 of these participants, four teacher educators, and 30 students. Data from observation protocols, semi-structured interviews, lesson documents, assessment tasks, and reflective journals were analyzed thematically and validated through source, method, and time triangulation. Descriptive ratings indicated stronger performance in inclusive classroom management (M = 3.5) and culture-based lesson planning (M = 3.2), but weaker performance in the use of culturally relevant media (M = 2.8) and culture-based assessment (M = 2.6). Triangulated evidence revealed a culturally responsive continuity gap: cultural responsiveness was evident in lesson planning and classroom interactions but diminished during assessment and critical reflection. When local cultural contexts were used as resources for mathematical reasoning rather than as decorative examples, students demonstrated clearer indicators of meaningful, mindful, and joyful learning. The study identifies authentic culture-based assessment, structured reflection, mentoring, and culturally relevant resources as priority areas for strengthening pre-service teachers’ pedagogical competence during teaching practicum.